Complementary and alternative medicine in children with diffuse intrinsic pontine glioma—A SIOPE DIPG Network and Registry study. Issue 9 (4th May 2021) - El‐Khouly, Fatma E.; Adil, Syed M.; Wiese, Maria; Hulleman, Esther; Hendrikse, N. Harry; Kaspers, Gertjan J.L.; Kramm, Christof M.; Veldhuijzen van Zanten, Sophie E.M.; van Vuurden, Dannis G.
Abstract: Introduction: Diffuse intrinsic pontine glioma (DIPG) is a rare and aggressive childhood brainstem malignancy with a 2‐year survival rate of <10%. This international survey study aims to evaluate the use of complementary and alternative medicine (CAM) in this patient population. Methods: Parents and physicians of patients with DIPG were asked to participate in a retrospective online survey regarding CAM use during time of illness. Results: Between January and May 2020, 120 parents and 75 physicians contributed to the online survey. Most physicians estimated that <50% of their patients used CAM, whereas 69% of the parents reported using CAM to treat their child during time of illness. Cannabis was the most frequently used form of CAM, followed by vitamins and minerals, melatonin, curcumin, and boswellic acid. CAM was mainly used with the intention of direct antitumor effect. Other motivations were to treat side effects of chemotherapy or to increase comfort of the child. Children diagnosed from 2016 onwards were more likely to use CAM (χ 2  = 6.08, p  = .014). No significant difference was found between CAM users and nonusers based on ethnicity (χ 2  = 4.18, p  = .382) or country of residence (χ 2  = 9.37, p  = .154). Almost 50% of the physicians do not frequently ask their patients about possible CAM use. Conclusion: This survey demonstrates that worldwide, a considerable number of patients with DIPG use CAM. Physicians should be more aware of potential CAM use and actively discuss the topic. In addition, more research is needed to gain knowledge about possible anticancer effects of CAM and (positive/negative) interactions with conventional therapies.